2014
DOI: 10.1155/2014/181072
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiles and Antioxidant and Antimicrobial Activities of the Leaves ofZanthoxylum bungeanum

Abstract: The ethanol crude extracts (ECE) and their subfractions from Zanthoxylum bungeanum leaves were prepared and their phytochemical profiles and antioxidant and antimicrobial activities were investigated. Moreover, the effective HPLC procedure for simultaneous quantification of twelve compounds in Z. bungeanum leaves was established. The correlation between the phytochemicals and antioxidant activity was also discussed. The ethyl acetate fraction (EAF) had the highest total phenolic (97.29 mmol GAE/100 g) and flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 39 publications
(40 reference statements)
0
26
0
2
Order By: Relevance
“…In the literature, wasn't found studies regarding the antimicrobial activity of the plant extracts of Z. caribaeum against the serotypes of Salmonella. However, Zhang et al (2014) reported the antimicrobial potencial whitin the genus against Gramnegative bacteria. According to the autors, ethanolic extract, ethyl acetate, acetone and methanolic of Zanthoxylum bungeanum showed MIC of 4.61 mg.mL , respectively, against the strain E. coli, corroborating with our study.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, wasn't found studies regarding the antimicrobial activity of the plant extracts of Z. caribaeum against the serotypes of Salmonella. However, Zhang et al (2014) reported the antimicrobial potencial whitin the genus against Gramnegative bacteria. According to the autors, ethanolic extract, ethyl acetate, acetone and methanolic of Zanthoxylum bungeanum showed MIC of 4.61 mg.mL , respectively, against the strain E. coli, corroborating with our study.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, leaves of Z. bungeanum are worthy of research because they also contain polyphenols and flavonoids with high antioxidant activity and can be used as a food additive (Li et al, 2015;Yang, Li, Tan, & Jiang, 2013). In our previous studies, according to the results of the structureactivity relationship of nine flavonoids from Z. bungeanum leaves (Zhang, Wang, Yang, Zhou, & Zhang, 2014b) and the correlation between the chromatographic fingerprint and antioxidant activity of the 22 subsequent fractions of Z. bungeanum leaves ethanol extracts (Zhang, Luo, Wang, He, & Li, 2014a;Zhang, Luo, & Wang, 2015), it was found that quercitrin, hyperoside, rutin, and afzelin were the dominant flavonoids, which played a major role in antioxidant and antimicrobial activity. Furthermore, hyperoside from Z. bungeanum leaves also exerts many bioactivities, such as antiproliferative effects against SW620 and antihyperglycemic and hepatocyte-protective effects (Zhang, Wang, Dong, Yu, & Zhang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study, the ZBM extract containing sanshool relax the facial muscles, we suppose the different effects are dose dependent with ionotropic mechanisms. Other constituents of the ZBM extract, such as flavonoids and polysaccharide, exhibit good antioxidant activities (Li, Zhou, Mou, & Mao, ; Zhang, Luo, et al, ; Zhang, Wang, et al, ) but their contribution to its anti‐wrinkle property may be weak.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ZBM is used in traditional Chinese medicine for the treatment of abdominal pain, dyspepsia, parasitosis, and eczema. Recent studies have revealed the many pharmacological effects of ZBM, including antibacterial, anti‐inflammatory, antioxidant, neuroprotective and anti‐ wrinkles (Artaria, Maramaldi, Bonfigli, Rigano, & Appendino, ; Tang et al, ; Yang et al, ; Zhang, Luo, et al, ).…”
Section: Introductionmentioning
confidence: 99%